PENGGUNAAN DAN MAKNA SETSUZOKUSHI ために DAN ように DALAM RAGAM TULIS (NHK ニュース) - Devi Risqi Indrawati; Sri Aju Indrowaty (Jurnal Pendidikan Bahasa Jepang Undiksha, 2023)
In Japanese, there are various kinds of setsuzokushi such as ために and ように. Many Japanese learners are confused in the use of these two setsuzokushi because they have the same but different function in the context of their use. This research uses a qualitative descriptive with observation method and literature study. This research aims to understand the usage and meaning of ために and ように correctly. The results are the use of ために combined with the first sentence which states the purpose that has been planned. Before ために is a dictionary form of verb or noun, verb that can be combined is verb which contains desires or intentions, whereas if a noun is added the particle の before ために. The use of ように is combined with the first sentence which states purpose or objectives of the condition. Verbs before ように are verbs that not contain desires or intentions but use dictionary or negative form potential verbs.